Molecular characterization of MT3 antigens by two-dimensional gel electrophoresis, NH2-terminal amino acid sequence analysis, and southern blot analysis. - Sorrentino, R (1985)
The monoclonal antibody 109d6, which recognizes major histocompatibility antigen MT3-like serologic determinants, has been used to characterize the molecules bearing this determinant in HLA-DR4 and -DR7 homozygous cell lines by two-dimensional gel and sequencing analyses. By these two criteria, these molecules are identical to each other. Southern blot analysis of genomic DNA from HLA-DR1 through -DR7 homozygous cell lines with DR beta-chain gene probes reveals a striking similarity in the pattern of hybridizing fragments between DR4 and DR7 haplotypes and among DR3, DR5, and DRw6 haplotypes reminiscent of the MT3/MT2 allodeterminant distribution. The sharing of the MT2 determinant between DR3, DR5, and DRw6 haplotypes and of the MT3 determinant between DR4 and DR7 haplotypes is part of a broader "homology," which may be a consequence of more recent separation of the haplotypes sharing the MT2 determinant on the one hand and the haplotypes sharing the MT3 determinant on the other hand.